THE LEARNING METHODS OF PROBLEM SOLVING SKILLS IN ISLAMIC BOARDING SCHOOL: DISCUSSION, EXERCISE, AND MODELING - Asmaúl Lutfauziah; Mimien Henie Irawati Al-Muhdhar; Suhadi Suhadi; Fatchur Rohman (JURNAL PENA SAINS, 2020)
The objective of this research describes the method of lecturers to teach problem-solving skills. Problem-solving skills is one of the skills needed in the 21st-century learning. Generally, Islamic boarding schools tend to use classic methods such as recitation, Bandongan, Sorogan. The study is survey research. It is a case study at the Islamic boarding school of Jagad ‘Alimussirry in the second semester of the academic year 2016/2017. Students live in Islamic boarding schools every day. The data were obtained through questionnaires and observations. Questionnaires were consisting of 12 items with a statement of Rosenberg's self-esteem scale. It’s given to the 46 students and five lecturers after learning. The respondents were randomly chosen. The study also conducted observations at the time of learning in 5 courses. Two observers made the observations. The results showed that the problem-solving skills had been taught with a "good enough" category. The learning method is discussion, exercise, and modeling. It is done with 5 phases of problem-solving. The findings are three methods to teach problem-solving skills in the Islamic boarding school. It is a discussion, exercise, and modeling with five problem-solving phases and six learning schemes. Therefore, this study can be used as consideration for education practitioners on how to teach problem-solving skills in Islamic boarding schools. Indonesia has 28 thousand Islamic boarding schools. In addition, this becomes a frequent correction to repair the learning of problem skills in Islamic boarding schools in Indonesia.